2014
DOI: 10.1371/journal.pone.0098581
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Measurement of Organic Acids in Tissues from Gastric Cancer Patients Indicates Increased Glucose Metabolism in Gastric Cancer

Abstract: The levels of organic acids representing metabolic pathway end products are important indicators of physiological status, and may be associated with metabolic changes in cancer. The aim of this study is to investigate the levels of organic acids in cancerous and normal tissues from gastric cancer patients and to confirm the role of metabolic alterations in gastric carcinogenesis. Organic acids in normal and cancerous tissues from forty-five patients with gastric adenocarcinoma were investigated by gas chromato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 27 publications
6
23
0
Order By: Relevance
“…Liquid chromatography-mass spectrometry (LC-MS) is the most common method of analysis. Several biomarkers have been proposed for GC diagnosis, prognosis, and surveillance[ 14 - 16 ]. Systematic reviews have demonstrated variation in the relative abundance of the metabolites of glycolysis, lactic acid fermentation, de novo lipid, and amino acid synthesis in biological samples of patients with GC compared with controls[ 13 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Liquid chromatography-mass spectrometry (LC-MS) is the most common method of analysis. Several biomarkers have been proposed for GC diagnosis, prognosis, and surveillance[ 14 - 16 ]. Systematic reviews have demonstrated variation in the relative abundance of the metabolites of glycolysis, lactic acid fermentation, de novo lipid, and amino acid synthesis in biological samples of patients with GC compared with controls[ 13 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In ginseng group, the composition was very similar to that of the normal control. A recent report revealed that the content of several compounds, including malic acid and 3-hydroxybutanoic acid, was significantly higher in tumor tissue compared to normal tissue (40). In our study, very high concentrations of malic acid and 2-hydroxybutanoic acid were also observed in the stool samples of the model group, which may have enhanced carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Normalized levels were then plotted as lines radiating from a common central point. The far ends of the 17 lines for ginseng samples were then joined together to produce star patterns for environmentally friendly and conventionally cultured roots using MS Excel program (Microsoft, Redmond, WA, USA), as described previously …”
Section: Methodsmentioning
confidence: 99%